Remarks at the Climate Adaptation Summit - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass spoke about how the World Bank recognizes and appreciates the Netherlands’ leadership and expertise on adaptation. He focused on action and adaptation, which is a core activity in the World Bank Group’s development activities. World Bank Group financing for adaptation increased from forty percent of climate finance in 2016 to over fifty percent in 2020. The Bank is committed to making it half of total climate finance for the next five years. In six West African countries, the World Bank Group is working to protect against coastal erosion, restore wetlands and mangroves, and build seawalls and dikes. He highlighted World Bank support for Risk Management Readiness Operations with Deferred Draw-Down Options in small island states across the Caribbean, Pacific and Africa to build institutions and strategies to handle national emergencies caused by natural disasters and to access instant funding when disasters strike. He spoke about steps taken to strengthen resilience in World Bank Group projects. He concluded by mentioning the World Bank's goal to help keep communities safe and to help them develop in ways that are resilient during climate change.